Conceptual framework on open government data usage and work productivity among public sector managers in Malaysia / Mohd Khairul Ezam Mohd Rasali, Shamila Mohamed Shuhidan and Mohammad Fazli Baharuddin - Mohd Rasali, Mohd Khairul Ezam; Mohamed Shuhidan, Shamila; Baharuddin, Mohammad Fazli (Faculty of Information Management, 2023)
The intent of this study was to investigate and comprehend the usage of open government data (OGD) and to take a look at the ways those roles affect public sector managers’ work productivity. Regardless of its novel reputation in the usage of OGD literature, past research has revealed that Malaysian public sector organisations have not entirely embarked on user OGD initiatives extensively. The main feature to note is that the data and information collected, maintained and kept by the government are national assets. The conceptual structure is composed of up of five independent variables: system quality, information quality, data availability, trust factor and voluntariness as well as two dependent: OGD usage and work productivity. There were six proposed hypotheses developed. The well-designed research notion provides the researcher with adequate trust to proceed to examining variables such as research design and data collection technique. It is believed that this proposal will enlighten relevant information on user of OGD among public manager and overall public sector ecosystem.